2002
DOI: 10.7202/002884ar
|View full text |Cite
|
Sign up to set email alerts
|

Selection Tests for Trainee Conference Interpreters

Abstract: This preliminary study devised and tested a series of psychometric tests to facilitate selection of simultaneous and consecutive interpreter-trainee candidates. Twelve tests, based either on text materials, linguistic subskills or speed-stress, were correlated with judges' ratings of the final interpretation examination. Students who passed the exam had higher mean scores on all tests than those who failed. Test scores were positively inter-correlated between completion-detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 0 publications
1
11
0
2
Order By: Relevance
“…Specifically, as the results of the individual strategy analyses have shown, those interpreting students with higher semester grades were those who more frequently employed strategies to overcome their language limitations by using body language (item 25), guessing from context (item 24), anticipating what the other person would say next (item 28) or using words or phrases with the same meanings (item 29). These findings echoed the results of several experimental studies on interpreting aptitude that found that associational and expressional fluencies as measured by synonym tests significantly correlated with interpreting performance (e.g., Gerver, Longley, et al 1989;Russo and Salvador 2004). Together, these findings suggested that the ability to paraphrase might be an integral part of interpreting aptitude.…”
Section: Relationship Between English Learning Strategies and Interprsupporting
confidence: 82%
“…Specifically, as the results of the individual strategy analyses have shown, those interpreting students with higher semester grades were those who more frequently employed strategies to overcome their language limitations by using body language (item 25), guessing from context (item 24), anticipating what the other person would say next (item 28) or using words or phrases with the same meanings (item 29). These findings echoed the results of several experimental studies on interpreting aptitude that found that associational and expressional fluencies as measured by synonym tests significantly correlated with interpreting performance (e.g., Gerver, Longley, et al 1989;Russo and Salvador 2004). Together, these findings suggested that the ability to paraphrase might be an integral part of interpreting aptitude.…”
Section: Relationship Between English Learning Strategies and Interprsupporting
confidence: 82%
“…Results from previous studies intended to predict successful performance in spoken-language interpreters indicated that verbal skills (verbal fluency and a rich vocabulary) are important factors for developing simultaneous interpreting and memory span for consecutive interpreting (Gerver et al 1989). So too are a strong motivation and the ability to grasp the links between various sequences and to analyze, reprocess and summarize the incoming message (Gringiani 1990).…”
Section: Predictors Of Sli Proficiencymentioning
confidence: 93%
“…The nature of the selection processes and aptitude testing before interpreting education has been widely examined in the literature on spoken-language interpreting (Longley 1978;Moser-Mercer 1985;Bowen & Bowen 1989;Gerver et al 1989;Longley 1989;Gringiani 1990;Lambert 1991;Martin & Abril 2002) and, to a lesser extent, also in the literature on signed language interpreting (Frishberg 1986;Humphrey 1994). It is known that each educational institution may set its own requirements according to private or public policies and the characteristics of the (spoken-or signed-language) interpreting course.…”
Section: Training Programmes For Signed Language Interpretersmentioning
confidence: 98%
“…Still others have approached aptitude from a more theoretical perspective and produced stimulating reflections: Lederer (1975) and Sofr (1976) drew attention to the concept of interpreting-related aptitude, and Alexieva (1993) focused on the role of short-term memory. Other publications provide descriptions of admission procedures with final-mark correlations (Arjona-Tseng 1994;Donovan 2003;Timarová & Ungoed-Thomas 2009) or of tests on abilities which proved predictive: lexical knowledge (Skaaden 1999), memory capacity 5 and verbal fluency, with particular reference to the production of synonyms (Gerver et al 1989), cloze tests (Gerver et al 1984;Moser-Mercer 1985;Lambert 1992b) and text processing strategies (Russo 1993;Russo & Pippa 2004). As to reports on tests, Shaw and Hughes (2006) provide the most recent extensive overview of the characteristics of second-language learners and sign language interpreters based on empirical studies with a view to suggesting evidence-based admission criteria to interpreter schools.…”
Section: What To Look For In An Interpreting Candidatementioning
confidence: 98%
“…As far as aptitude for spoken-language interpreting is concerned, the first most comprehensive and methodologically sound aptitude test was developed by Gerver et al (1984Gerver et al ( , 1989 and was implemented at the Polytechnic of Central London. The authors concentrated on the second of the several qualities expected in a candidate (see Table 1, column 4: "Ability to grasp rapidly and to convey the essential meaning of what is being said") and suggested twelve tests of three different types: 1) text-based tests, which assume the processing of connected discourse to be a crucial feature of the interpreter's task; 2) subskill-based tests aimed at assessing verbal ability; 3) stress-based tests aimed at assessing performance under time pressure.…”
Section: Predictive Aptitude Testsmentioning
confidence: 99%